A LITERATURE REVIEW : SOCIAL STUDIES LEARNING STRATEGIES FOR SLOW LEARNER STUDENTS IN INCLUSIVE EDUCATION PROGRAMS IN ELEMENTARY SCHOOLS - Yawma Wulida; Sapriya; Nouval Nanola (International Conference on Elementary Education, 2024)
This article aims to discuss social studies learning strategies for slow learner students in inclusive education programs in elementary schools. The research method used is a literature study to obtain an overview of Social Sciences learning strategies for slow learner students in the inclusive education program based on several experts and based on a study of supporting references. The focus of the discussion in this research is the application of several social studies learning strategies for slow learner students in inclusive schools which aims to help slow learner students understand and master social studies learning material more effectively. Learning strategies for social studies subjects for slow learner students can be done in several ways such as positioning at the front of the class, using visual material to illustrate social studies concepts, simplifying learning material, asking open questions, using concrete examples to illustrate concepts in social studies. Teachers can also repeat material that has been taught, using technology or learning aids specifically designed for slow learners, dividing students into small groups, provide continuous feedback to slow learner students in the form of short questions, simple quizzes, or class discussions to regularly monitor student understanding. To support slow learner students in learning Social Sciences in inclusive education programs in elementary schools, teachers should use learning strategies that focus on inclusion and adaptation.